A First Step Up the Energy Ladder? : Low Cost Solar Kits and Household's Welfare in Rural Rwanda - Grimm, Michael; Munyehirwe, Anicet; Peters, Jorg; Sievert, Maximiliane (World Bank, Washington, DC, 2016)
More than 1.1 billion people in developing countries are lacking access to electricity. Based on the assumption that electricity is a prerequisite for human development, the United Nations has proclaimed the goal of providing electricity to all by 2030. In recent years, Pico-Photovoltaic kits have become a low-cost alternative to investment intensive grid electrification. Using a randomized controlled trial, the paper examines uptake and impacts of a simple Pico-Photovoltaic kit that barely exceeds the modern energy benchmark defined by the United Nations. The authors find significant positive effects on household energy expenditures and some indication for effects on health, domestic productivity, and on the environment. Since only parts of these effects are internalized, underinvestment into the technology is likely. In addition, our data show that adoption will be impeded by affordability, suggesting that policy would have to consider more direct promotion strategies such as subsidies or financing schemes to reach the UN goal.